A general theory of power concentration: demographic influences on political organization. Issue 4 (1st June 2018) - Gerring, John; Maguire, Matthew; Jaeger, Jillian
Abstract : Why is the exercise of political power highly concentrated in some polities and widely dispersed in others? We argue that one important causal factor is demographic. Populous polities are characterized by less concentrated structures of authority. To explain this relationship, we invoke two mechanisms: heterogeneity and trust. The theory is demonstrated with a wide variety of empirical measures in cross-country analyses including most sovereign states and extending back to the 19th century. The result suggests the possibility of a ubiquitous 'law' of politics.